Tenure Security and Responsible Land Management of Urban Informal Settlements on Waqf Land in Semarang City, Indonesia - Iwan Rudiarto; Walter Timo de Vries; Alvita Bhanuningtyas Rustanto; Kanaya Aliyanadira Hidayat (Land)
The major challenge facing big cities in developing nations is allocating residential land to the urban poor, given the constraints on land availability. This article investigates how and why the management of Waqf land, a particular type of land tenure in urban informal settlements, transforms. The analysis draws on principles of responsible land management and focuses on the specific case of Waqf land owned by the Kauman Grand Mosque in Semarang City, Indonesia. With a questionnaire distributed among tenants of the Waqf land, it was possible to retrieve data on experiences with the management of the Waqf land. The questionnaire and subsequent analysis used a scoring sheet based on the 8R framework of responsible land management. The findings indicate that the management of Waqf land in the study area changed and improved over time, evolving from an informal to a more formal structure. The responses additionally demonstrate a gradual transformation whereby, gradually, nearly all aspects of the 8R framework of responsible land management are considered positively. Nevertheless, the aspects of reflexivity and retraceability still score low, as access to documentation is still limited, and evaluations of how effective the management of land is are infrequent. The study concludes that despite being an unconventional form of land management, the Waqf land tenure regime appears to secure informal types of urban tenure, especially in areas with limited land availability. Moreover, the Waqf land institution supports strong and cooperative relationships within the community.